The Roles of Sensory Attributes, Functional Benefit, and Brand Ambassador Toward the Brand Loyalty and Repurchase Intention of a Coffee Brand - Christian Haposan Pangaribuan; Putri Paulina; Dairion Thahar (Universitas Pendidikan Ganesha, 2020)
The trend of drinking coffee has resulted in an increase of coffee consumption around the world, including Indonesia. This study investigates the roles of sensory attributes, functional benefit, and brand ambassador towards the intention to repurchase which leads to brand loyalty of Luwak White Coffee. This study uses a quantitative approach by using primary data and distributed questionnaires to 100 employees of various corporations in Jakarta. The data was analyzed through regression analysis. The result of this study shows that functional benefit has a significant influence on both intentions to repurchase and brand loyalty. This benefit factor is the most important precedent to both repurchase intention and brand loyalty. On the other hand, sensory attributes do not affect repurchase intention. This type of information can be important to predict or to explain the market response to luwak coffee products, and also to select which sensory attribute should be included in a sensory specification or must be considered in product quality control programs. Another important finding is that, contrary to our expectations, we do not find empirical support for the significant influence of brand ambassador on an intention to repurchase and brand loyalty. The explanation may be that customers currently expect the functional benefit in the form of healthier gastric-friendly white coffee. Moreover, the brand ambassador may not be too influential in the high buying decision among luwak coffee consumers. The relevant contributions that emerged from this study include not only bridging the aforementioned gap in the literature but also offering significant managerial implications to assist organizations to understand the importance of functional benefits toward repurchase intention and brand loyalty.